Systematic Literature Review: Peran Religiusitas terhadap Kualitas Perkawinan di Indonesia - Yustinus Phoebe Setiawan; Mulya Virgonita Iswindari Winta; Margaretha Maria Shinta Pratiwi (Yayasan Literasi Sains Indonesia, 2026)
Marriage in Indonesia is not merely considered a social or legal bond, but also a sacred institution strongly shaped by spiritual and religious values. This study aims to explore the role of religiosity in predicting marital quality through a systematic literature review (SLR). A total of 15 journal articles published between 2015 and 2025 were analyzed, each focusing on the intersection between religiosity and marital dynamics. The findings indicate that religiosity demonstrates a positive correlation with marital satisfaction, happiness, and long-term commitment. Religiosity functions as a moral foundation in building household harmony and an adaptive mechanism to overcome various marital challenges such as conflict, economic pressure, and personality differences. Religious values encourage spouses to foster mutual respect, forgiveness, and loyalty, thereby maintaining the stability and harmony of the relationship. Consequently, religiosity emerges as a central factor in achieving sustainable marital quality and resilience. This review highlights the role of religiosity in strengthening marriages in Indonesia and offering insights for both researchers and practitioners in family and social studies.